Kearifan lokal Tradisi Mappatabe’ Masyarakat Bugis Bone pada Generasi Milenial Desa Ujung Tanah Kecamatan Mare Kabupaten bone - Muhammad Rusdi; Muhammad Yanis; Ilham Ilham; Andi Tabrani Rasyid; Nurmi Nurmi; Arjuna Sakti Pratama (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to find out the aesthetic description of the Mappatabe tradition of the Bugis Bone Community in the Millennial Generation. The type of research used is field research with a focus on studies on the aesthetic description of the millennial generation's mappatabe tradition as a Bugis cultural identity. The subjects in this study were community leaders, youth and humanists as well as educators. The research instrument uses key instruments so that the research activities are systematic and easy. The authors use the form of instruments, namely the key instruments are the researchers themselves as data collectors through observation and interviews. The data obtained was then analyzed, reduced in data, presented data and verified conclusions